A health service for the nation (London : published by the Women Public Health Officers' Association)
1943-03-27 1943 1940s 8 pages 21. In the Health Centre all the personal health records of every person in the district served by the Centre should be kept, and should be available to the medical staff of the Divisional Treatment Centre or Regional Hospital. Health Centres would be administered by the Regional Health Department and not by the Regional Hospital. We suggest that the Home Doctors using the Health Centre should not be responsible for its general working nor that one of them should become its Medical Superintendent, as is suggested in the draft interim report of the Planning Commission published by the British Medical Association, 1942. A senior Health Visitor should be responsible to the Regional Medical Health Officer for the cleanliness and good order of each Health Centre and for the co-ordination of all ancillary services desired by the Medical Staff. 22. As Health Centres should be primarily centres for health education as well as for Home Doctors' service and, as the National Health Service develops, for periodical medical and dental examination of the whole community, we suggest that they should be much more numerous than the Divisional Treatment Centres which will serve that minority of the population needing medical treatment outside the range of the Maternity and Child Welfare Service and beyond the competence of the general practitioner or Home Doctor. 23. We suggest that a local Health Centre should be not more than two miles — in densely populated districts it should be less — from every town or village home in England. No child can be compelled to walk more than two miles to school : it is the duty of the Local Education Authority to see that a school is available within that distance. Similarly, we believe that it should be the duty of the Regional Health Authority to provide enough Health Centres to be easily accessible to all the inhabitants of all towns and villages. 24. BUILDINGS. Where satisfactory buildings for Maternity and Child Welfare and/or School Medical Services already exist, we suggest that these should become Local Health Centres, additional accommodation being provided where necessary for the Home Doctors and for the clerical and other staff needed for the extended services based on the Health Centre. In some cases existing doctors' rooms in Maternity and Child Welfare Centres could be available for use at times convenient to the Home Doctors and their patients. 25. Where a new Health Centre is required, we suggest that this should not, as a rule, be under the same roof as a Divisional Treatment Centre, but may well form part of a larger building provided for some other form of social service, e.g., a school, Day Nursery, a Community Centre, or a Citizens' Advice Bureau. Some of our members have been impressed with the practical advantages accruing from this arrangement in the organisation of local health and social services in Toronto and New York. Five 292/847/2/155